Mecanismos envolvidos na indução de dor de cabeça após o estresse: uma revisão sistemática de estudos clínicos e avaliação de modelo animal - Viero, Fernanda Tibolla (2024)
Primary headaches, including tension-type headache (TTH) and migraine, comprise the most prevalent neurological disorders globally. Although TTH is more prevalent, migraine is more debilitating and significantly affects the quality of life of affected patients. Both pathologies are more prevalent in women. Despite this, these headaches are often inadequately treated, and most patients are refractory to treatments, in part due to challenges in identifying the underlying pathophysiological mechanisms. Furthermore, stress is a common factor in triggering TTH and migraine attacks. However, there were still no systematic review studies linking stress, TTH and migraine. Thus, the first study highlights the association between mental/cognitive stress and perceived daily stress with increased pain perception, headache development, and transient pain intensity in patients with migraine and TTH. Furthermore, there were no preclinical models that mimicked migraines triggered by stress. Thus, here it was first demonstrated that unpredictable noise stress induces migraine-like inflammatory behaviors and parameters, with sexual difference. Subsequently, we investigated the role of the TRPA1 receptor in sound stress-induced migraine. Stress has been shown to cause nociception and neurogenic inflammation, with implications for redox regulation and antioxidant factors, evidencing a sexual influence. Using pharmacological and genetic tools, TRPA1 was found to play a crucial role in inflammation and oxidative stress associated with migraine, pointing to this receptor as a potential therapeutic target for migraine. Taken together, these studies provide a comprehensive overview of the complex interactions between stress, neurogenic inflammation, TTH, and migraine, indicating possible directions for future investigation and therapy development.